RANCANG BANGUN APLIKASI PENJUALAN BUKET PADA TOKO CE_FLORIST DI KABUPATEN PALI BERBASIS ANDROID - Dendi Apriansya; Yuntari Purbasari; Nurmayanti Nurmayanti (STEKOM PRESS, 2024)
providers bouquet products for the community, which is located at Jalan GG. RT.015 Mosque RW.005 Talang Ubi Timur Village, Talang Ubi District, Penukal Regency Abab Lematang Ilir. South Sumatra Province. The lack of information conveyed to the public, resulting in a lack of knowledge the community regarding the sales of the ce florist shop in PALI district due to the sales information system that was carried out at the ce florist bouquet shop is still manual, namely people who want to know about the latest information about bouquet items must come directly so that it is more effective and efficient, because it takes a lot of time to arrive at the ce florist's bouquet shop. So from the researcher will make an android information system for the ce florist bouquet shop which will be accessed through the application that we install using Flutter programming language. This study uses the method (SDLC) Waterfall as a development method to be used when designing and build applications, while the research methods to be used is a descriptive method through a qualitative approach. Research collecting data through direct observation, interviews and library research. help tool uml design to help design the system to be created. With the existence of this android application hopefully helps people save time when want to shop at the ce florist bouquet shop.